Effects of riboflavin and amotosalen photoactivation systems for pathogen inactivation of fresh‐frozen plasma on fibrin clot structure. Issue 1 (10th September 2015) - Hubbard, Thomas; Backholer, Lucy; Wiltshire, Michael; Cardigan, Rebecca; Ariëns, Robert A.S.
Abstract : BACKGROUND: Fresh‐frozen plasma (FFP) transfusion carries a risk of viral transmission from donor to recipient. Riboflavin (Mirasol) and amotosalen (Intercept) are two pathogen inactivation (PI) methods that may enhance the safety of FFP for transfusion. Our study investigated the effects of Mirasol and Intercept treatment on fibrin formation and clot structure. STUDY DESIGN AND METHODS: FFP underwent either Mirasol or Intercept treatment, and aliquots were taken before addition of the compound, before illumination (after addition of compound only), and after treatment (addition of compound plus illumination). All samples underwent turbidimetric analysis, lysis analysis, assessment of clot permeation, and analysis by laser scanning confocal microscopy. RESULTS: After treatment, there was a decrease in optical density of the fibrin network for Mirasol and Intercept, lag time to fibrin formation was prolonged for Mirasol and lysis time for Intercept, clot permeability was significantly decreased, and clot density was increased for both. CONCLUSIONS: Our study shows that plasma treated with Mirasol and Intercept produces denser clots consisting of thinner fibers and warrants further studies to evaluate the clinical significance of these structural changes in fibrin clot formation.